A monocytogenic humoral factor released after lymph node stimulation - Willoughby, D. A. (1967)
The injection of complete Freund's adjuvant or certain other preparations directly into the cervical lymph nodes of rats is followed by a striking, prolonged monocytosis. The monocytosis may be transmitted passively with serum and is thought to be due to a hormone elaborated by appropriately stimulated lymphoid tissue and acting on the marrow or elsewhere. It is suggested that proliferation of mononuclear phagocytes in inflammation, delayed hypersensitivity, cellular immunity and antibody production may be associated with similar stimulation of lymphoid tissue followed by hormonal release. Animals inoculated in neonatal life with extracts of lymph nodes (a procedure that suppresses certain delayed hypersensitivity reactions) failed to developed a monocytosis when stimulated in adulthood or when given active serum from stimulated normal rats. Neonatally treated animals, however, after lymph node stimulation in adulthood do produce a serum factor capable of transmitting monocytosis to normal rats. The results imply that the action of the monocytogenic hormone may be largely dependent on a state of specific natural hypersensitivity whose development depends on absence of the hormone from the immature lymphoid tissue present in foetal and neonatal life. It is postulated that injection of the hormone in early life suppresses the proliferation of those clones that produce the antibody on which hypersensitivity in adulthood depends. The suggestion is made that a similar mechanism may explain the ability of various other hormones to act at very low concentrations.